Synthesis and characterization of fenofibrate–atorvastatin calcium cocrystals with Para-Aminobenzoic Acid as a Coformer: Design, formulation, and evaluation - Ashwin Kuchekar, Anirudha Chavan, Poonam Inamdar, Ashwini Ramkrishana Gawade (Journal of Applied Pharmaceutical Science, 2025)
This study aimed to improve the dissolution profile of two poorly soluble drugs, atorvastatin calcium and fenofibrate, through cocrystallization via carefully selected coformers. Five different coformers were screened via a molecular docking approach with the PyRx virtual screening tool. Binding energy and hydrogen bond formation data identified para-aminobenzoic acid (PABA) as the most suitable coformer for cocrystal formation. The cocrystallization process was carried out via the liquid-assisted grinding method. The resulting cocrystals were characterized via Fourier transform infrared (FT-IR), powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), and scanning electron microscope (SEM) techniques. A detailed evaluation of fenofibrate, atorvastatin calcium, and fenofibrate−atorvastatin calcium-PABA multidrug cocrystals revealed improved solubility compared with that of the pure drugs. Characterization through FT-IR confirmed interactions between the drugs and the coformer, whereas PXRD, DSC, and SEM analyses supported the formation of a distinct crystalline phase. An in vitro dissolution study demonstrated a significant increase in the dissolution rate of the cocrystals. The findings concluded that cocrystals prepared with PABA via the liquid-assisted grinding method successfully improved the solubility of atorvastatin calcium and fenofibrate, providing a promising approach to address the challenges associated with poorly soluble drugs. The novelty lies in the strategic combination of two lipid-lowering agents into a single multicomponent crystal system, offering improved solubility, dissolution rate, and potential bioavailability compared to their standalone forms. This work pioneers the application of pharmaceutical cocrystallization for dual-drug delivery in dyslipidemia management, offering a promising platform for fixed-dose combination therapies with enhanced patient compliance and therapeutic synergy.
Keywords: Novel drug delivery, cocrystallization, coformer, fenofibrate, atorvastatin calcium